Knowledge and Practice regarding Post-Partum Intra-Uterine Contraceptive Device among Antenatal Women Attending AMDA Hospital, Jhapa - Dhimal, Sita; Ghising, Rashmi; Dahal, Nirmala; Jha, Nilam Kumari; Shah, Rekha; Bhandari, Bhawana (Journal of Advanced Academic Research, 2023)
Introduction: Family planning was set up in 1936. It was at first known as the sex hygiene and birth regulation society. Intrauterine contraception is one of the most cost-effective methods of contraception. PPIUCD can be inserted in 48 hours postpartum, referred to here as postpartum intrauterine contraceptive device. Failure to plan a pregnancy can adversely affect the health of the family as a whole. High parity is related to increased maternal, perinatal and infant deaths and is associated with nutritional problems of both mother and child. Objectives: The aim of this study is to assess knowledge and practice regarding PPICUD among the Antenatal mothers attending AMDA Hospital, Damak, Jhapa. Methodology: A cross-sectional observational design was used for the study. One hundred sixty-four antenatal mothers will be taken in the study. Self-administered questionnaire and interview method used for the study. Data will be summarized using descriptive statistics and inferential statistics. Results: One hundred sixty-four antenatal mothers participated in the study, 121 antenatal mothers (73.8%) had moderate, 20 antenatal mothers (12.2%) had adequate and 23 antenatal mothers (14%) had inadequate knowledge. there was a significant association between knowledge with age, sex, religion, educational status, marital status, type of family, occupation, type of family, monthly income, parity, pervious source of information. Conclude: The study concludes that awareness and knowledge among antenatal mothers are high but the usage is low. Many educational and motivational activities are needed.